Comparative Hagiology Issues in Theory and Method - Rondolino, Massimo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue engages with questions of theory and methods in the comparative, cross-cultural study of hagiographical sources. As such, it offers, first and foremost, the venue for conducting a scientific discussion on a (re)definition of "hagiography". It also allows for the identification of shared approaches and methodologies in the study of material that may be apprehended through this categorization, as an effective strategy for the study of religious phenomena. To achieve this, the present volume brings together a selected number of scholars, whose work focuses on the theoretical study of "hagiography" and the historical examination of hagiographical sources. In this Special Issue, five core essays put forward propositions for the comparative and cross-cultural (re)definition of "hagiography", to which further contributors respond, eventually providing a vibrant collaborative debate on a core theoretical and methodological issue in religious studies at large.